1990
DOI: 10.1111/j.1751-1097.1990.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Fluorescence Concentration Quenching of Flavomononucleotide in Glycerine‐water Solutions

Abstract: We measured concentration changes of the fluorescence quantum yield eta/eta 0 of flavomononucleotide (FMN) in glycerine-water solutions of various viscosities. The results obtained show that FMN dimers are traps for the exciting light energy as well as the energy transferred non-radiatively. Very good agreement between the experimental and theoretical eta/eta 0 results was obtained. It has been shown that in the investigated solutions non-radiative energy transfer from monomers to dimers takes place, preceded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…(10) and (11)) for the description of concentration dependent data of fluorescence quantum yield and emission anisotropy of FMN in glycerol-water solutions of different viscosities η′ = 0.056 Pa s (GWI) and 0.256 Pa s (GWII) has shown that multistep energy transfer takes place in the monomer and dimer systems [69,70]. The excitation energy can visit different monomers M* prior its transfer to FMN dimers D:…”
Section: Nonradiative Energy Transfer Between Fmn Molecules In Viscoumentioning
confidence: 98%
See 4 more Smart Citations
“…(10) and (11)) for the description of concentration dependent data of fluorescence quantum yield and emission anisotropy of FMN in glycerol-water solutions of different viscosities η′ = 0.056 Pa s (GWI) and 0.256 Pa s (GWII) has shown that multistep energy transfer takes place in the monomer and dimer systems [69,70]. The excitation energy can visit different monomers M* prior its transfer to FMN dimers D:…”
Section: Nonradiative Energy Transfer Between Fmn Molecules In Viscoumentioning
confidence: 98%
“…The first reports on qualitative and quantitative properties of energy transport for FMN appeared in 1990 and were based on the Bojarski theory of multistep excitation energy transfer: the theory of photoluminescence concentration quenching (PLCQ) [69] and the theory of concentration depolarization of photoluminescence (CDPL) [70]. Table 2).…”
Section: Nonradiative Energy Transfer Between Fmn Molecules In Viscoumentioning
confidence: 99%
See 3 more Smart Citations